Investigating Primary School Children’s Creative Potential Through Dynamic Assessment - Zbainos, Dimitrios; Tziona, Athanasia (Frontiers in Psychology, 2019)
This paper focused on examining primary school students’ creative potential through dynamic assessment. The study was carried out through a quasi - experimental design. The sample consisted of ninety Greek primary school students between fourth and sixth grade who were randomly divided into a group that received dynamic assessment (N =37) and a control group (N = 53). Both groups were initially tested with the graphic-artistic form of the Evaluation of Potential Creativity (EPoC) test. The dynamic assessment group received mediation with graduated prompting while no such treatment was applied the control group, and both groups were post-tested. The results demonstrated that mediation significantly improved dynamic assessment group’s creative potential. It appeared that dynamic assessment contributes in exhibiting a clearer portrait of students’ creative potential which can be of valuable assistance to nurturing creativity.